Respuesta :

25792
Basically the answer is 6, if you'd like an explanation, let me know. :)
Answer: 6.

Explanation:

The picture is blur.

I got that answer and will explain you the solution assuming the expression is:

8 + 24 ÷ (2 x 6) - 4.

Before adding 8 to 24 ÷ (2 x 6) you have to solve 24 ÷ (2 x 6).

Start by solving the parenthesis: (2 X 6) = 12

Now perform the division: 24 ÷ 12 = 2

Now you can add and subtract: 8 + 2  - 4 = 10 - 4 = 6.

You can perform these operations directly in an ordered way:

8 + 24÷(2x6) - 4 = 8 + 24÷12 - 4 = 8 + 2 - 4 = 6